Sustained ocular delivery of Dorzolamide-HCl via proniosomal gel formulation: in-vitro characterization, statistical optimization, and in-vivo pharmacodynamic evaluation in rabbits - Nagwa Hussein Fouda; Randa Tag Abdelrehim; Doaa Abdelmagid Hegazy; Basant Ahmed Habib (Taylor & Francis Group, 2018)
Glaucoma is the second cause of blindness worldwide. Frequent administration of traditional topical dosage forms may lead to patient incompliance and failure of treatment. Our study aims to formulate proniosomal gel formulations that sustain the release of the water-soluble anti-glaucoma drug Dorzolamide-HCl (Dorz). Proniosomal gel formulations were prepared using coacervation phase separation method according to a 52 full factorial design. The effects of Cholesterol and surfactant (Span 40) amounts (independent variables) on the percentage entrapment efficiency (EE%), particle size (PS), and the percent of drug released after 8 h (Q8h) (dependent variables (DVs)) were investigated. An optimized formulation (OF) was chosen based on maximizing EE% and Q8h and minimizing PS. An intraocular pressure (IOP) pharmacodynamic study was performed in rabbits to evaluate the in-vivo performance of the OF-gel compared to the marketed Trusopt® eye drops. The results showed that the independent variables studied significantly affected EE%, PS, and Q8h. OF was the one containing 60 mg Cholesterol and 540 mg Span 40. It had desirability of 0.885 and its actually measured DVs deviated from the predicted ones by a maximum of 4.8%. The in-vivo pharmacodynamic study showed that OF could result in higher reduction in IOP, significantly sustain that reduction in IOP and increase Dorz bioavailability compared to Trusopt® eye drops. Thus the OF-gel is very promising for being used in glaucoma treatment.